PENGARUH EFIKASI DIRI TERHADAP KINERJA PNS GURU SMAN WILAYAH II JAKARTA PUSAT - Rohman Hidayatul Attoriq (Fakultas Keguruan dan Ilmu Pendidikan Universitas Nahdatul Ulama Indonesia, 2020)
The objective of this research is to obtain information about the effect of self efficacy on performance. It was quantitative research with survey method in SMA N region II Central Jakarta.The research was conducted to all civil servant teachers by using a survey method with path analysis applied in testing hypothesis. The number 117 civil servant teachers as sample was selected by using Slovin formula.The research conlude: There is a direct positive effect of self efficacy on performance.